Study on employee's perception of performance evaluation system in PSZ - P'ng, Keng Bie, 1990-, author; Mohamed Fuad Ahmad, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda (Perakaunan)) - Universiti Teknologi Malaysia, 2013